The Amulet of Samarkand - Stroud, Jonathan (New York : Hyperion Books For Children, 2003)
Nathaniel, a magician's apprentice, summons up the djinni Bartimaeus and instructs him to steal the Amulet of Samarkand from the powerful magician Simon Lovelace.
"Miramax books."
Includes bibliographical references.
UNCP 307070.
UNCP c. second printing.
Keywords: Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Apprentices -- Juvenile fiction; London (England) -- Juvenile fiction; England -- Juvenile fiction